Unexpected Infective Endocarditis in Corrected Congenital Heart Disease: A Case Report - Cool, Charlotte Johanna; Serulina, Rachmi; Saboe, Aninka (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To describe patients with corrected Congenital Heart Disease (CHD) who experienced Infective Endocarditis (IE).Methods: Two cases of IE were observed in 2019. The first case involved a 36-year-old woman with previous percutaneous transcatheter perimembranous ventricular septal defect (VSD) closure four months before admission. Echocardiography showed vegetation at noncoronary cusps of the aortic valve. Patient received antibiotics for six weeks and underwent surgery for evacuation of vegetation and device, along with VSD closure with a cardiovascular patch (Gore-tex). The second case involved a 43-year-old woman with a history of surgical closure in secundum atrial septal defect (ASD) by pericardial patch two months before admission. Echocardiography showed vegetation at the tricuspid valve. Patient received antibiotics for four weeks and planned for surgery to evacuate vegetation. Results: IE is one of the major complications in CHD, whether uncorrected, treated, or corrected. The risk of IE increased with an invasive procedure. Post closure IE is rare. Poor dental hygiene and immunocompromised also increased patient's risk to be exposed to IE as shown in the first patient who had dental caries and the second patient who was on methylprednisolone for post-surgical pericardial effusion treatment. Conclusion: The risk of IE increases with invasive procedures in CHD patients. Although the incidence of IE is quite rare, its possibility should become of a serious concern among physicians.